2013
DOI: 10.1007/s00468-013-0941-6
|View full text |Cite
|
Sign up to set email alerts
|

Increasing relevance of spring temperatures for Norway spruce trees in Davos, Switzerland, after the 1950s

Abstract: Key message Relevance of spring temperatures for tree-ring growth steadily increased since 1950s. Closely linked tree-ring growth and net CO 2 exchange driven by spring temperatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Ring width was slightly and positively related to spring temperatures (Churakova et al, 2014 ), but also to precipitation in September of the previous growing season and in current June (Figures 5A,B ). In accordance, Mäkinen et al ( 2002 ) found that precipitation during the growing season at low altitude sites (130 m a.s.l.)…”
Section: Discussionmentioning
confidence: 90%
“…Ring width was slightly and positively related to spring temperatures (Churakova et al, 2014 ), but also to precipitation in September of the previous growing season and in current June (Figures 5A,B ). In accordance, Mäkinen et al ( 2002 ) found that precipitation during the growing season at low altitude sites (130 m a.s.l.)…”
Section: Discussionmentioning
confidence: 90%
“…There is a rich body of literature on changes in 13 C isotopic discrimination and iWUE and on observational evidence from δ 13 C tree-ring records McCarroll and Loader, 2004;Fichtler et al, 2010;Leonardi et al, 2012;Churakova , Sidorova, S;Lévesque et al, 2014;Liu et al, 2014b;Saurer et al, 2014;Hartl-Meier et al, 2015;Voelker et al, 2016), free-air CO 2 enrichment (FACE)-type experiments (Battipaglia et al, 2013;Klein et al, 2016), δ 13 C site measurements (Pataki et al, 2003;Bowling et al, 2014), and δ 13 C paleodata (Voelker et al, 2016). These data generally suggest small to moderate decadal-to-century-scale changes in discrimination that correspond to a 20th century increase in iWUE On the order of 20 % and physiological control towards a constant ratio of the partial pressure of CO 2 within the leaf's substomatal cavities to the CO 2 pressure outside the leaf (c i /c a ; Saurer et al, 2004;Leonardi et al, 2012;Frank et al, 2015) and, more generally, a pattern of stomatal optimization towards minimizing water loss per unit carbon assimilated (Voelker et al, 2016).…”
mentioning
confidence: 99%
“…Investigating spruce and larch, Koprowski (2012Koprowski ( , 2013) also found a significant degree of influence thanks to changing climatic conditions in Poland, noting that rising temperatures in February and March can decrease tree resistance to low temperatures, making them more vulnerable to late winter-early spring frosts. In contrast, Churkova et al (2014) in their study of spruce found that a rise in temperature in spring has a positive effect on tree-ring formation in the Swiss Alps at high altitudes.…”
Section: Introductionmentioning
confidence: 85%